2006
DOI: 10.1002/ajhb.20554
|View full text |Cite
|
Sign up to set email alerts
|

Serum cobalt in children with essential hypertension

Abstract: The effect of cobalt on the cardiovascular system is one of many aspects of cobalt metabolism in humans. Elastin and collagen are the main proteins of the vascular wall. The aims of this study were: 1) to determine serum cobalt concentrations in children with hypertension; and 2) to study the correlation between serum cobalt and some biological markers of the extracellular matrix of the vascular wall, i.e., anti-elastin and anti-collagen type IV antibodies. Patients showed statistically significant higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The literature on Co levels in children includes studies on this element’s status in children with iron deficiency anemia [ 31 ], severe malnutrition [ 32 ], and hypertension [ 33 ]. In the available literature, we found one study, which was already mentioned, on the serum and urine Co balance in four adult patients receiving PN.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on Co levels in children includes studies on this element’s status in children with iron deficiency anemia [ 31 ], severe malnutrition [ 32 ], and hypertension [ 33 ]. In the available literature, we found one study, which was already mentioned, on the serum and urine Co balance in four adult patients receiving PN.…”
Section: Discussionmentioning
confidence: 99%
“…1,2022 cardiovascular diseases 20 metabolism in humans. A study on children with essential HTN showed significantly higher systolic and diastolic blood pressure and significantly lower serum cobalt concentrations than controls [49]. Oxidative stress, inflammation, and apoptosis are pathologic mechanisms in rats' CoCl2 induced HTN and cardiovascular complications [50].…”
Section: Variation Of Serum Trace Element Levels Inmentioning
confidence: 99%
“…Nicoloff et al [12] determined serum cobalt concentrations in children with hypertension. Cobalt is known to be associated with hypertension in adults.…”
Section: Identification Of Causementioning
confidence: 99%